Literature Study: Effectiveness of Scabies Treatment Using Natural Ingredients - Glory Merys Melanesian Nega; Erina Yatmasari; Agustnus Sareh Arjono Tjandra (Universitas Wijaya Kusuma Surabaya, 2022)
The skin is the outermost organ that is often exposed to the external environment, which can cause skin diseases, one of which is scabies. Scabies is caused by the mite Sarcoptes scabiei var hominis and its products. often found in densely populated environments, such as Islamic boarding schools and communities with poor personal hygiene quality or tend to be poor, and low economic status. For management, administration of drugs is generally topical to kill the mites that cause this disease. However, it has limitations, such as the relatively expensive price, so that alternative medicine materials with relatively cheaper costs are needed, namely medicines made from plants. The purpose of this study was to evaluate publications on the effectiveness of scabies treatment using natural ingredients. Methods: This study uses a literature study method in obtaining information or data from journals and research documents. The results of the literature study indicate that the use of traditional medicine is effective in the healing process of scabies. The use of traditional medicine is effective in curing scabies but as a complement to the use of topical drugs.